Climate change and development - Tanner, Thomas, 1975-; Horn-Phathanothai, Leo (Routledge; Londond, 2014)
"This text provides a comprehensive and multi-disciplinary entry level account of the challenges, the response, and the alternative pathways to tackling development in a changing climate. The first section provides the building blocks for understanding and framing the climate-development nexus. It will include an overview of the science, drivers and impacts of climate change, and present the different disciplinary perspectives. The second section presents and assesses responses to the development challenges posed by a changing climate at different spatial scales. This section will address international, regional, national, sub-national and non-governmental responses to climate change. It will also include an overview of the main instruments and competing approaches for addressing climate change as a development concern, including market-based measures, regulatory instruments, and voluntary agreements. The final section will be forward looking and solutions-oriented. It will set out different critiques of 'development-as-usual' and competing visions of development in a warming and carbon-constrained world. A description of the changing context of development, shaped by the interlocking challenges of poverty, energy, growing natural resource scarcities, deteriorating ecosystems and climate change will help to situate the debate about alternative modes of development. This section lays out the intellectual and scientific underpinnings of the Green Economy, and presents it as an alternative to GDP-centric conceptions of development, one that is consistent with climate change adaptation and mitigation whilst also contributing to social justice and poverty reduction"--
Includes bibliographical references (pages 332-356) and index.
Keywords: Economic development -- Environmental aspects; Sustainable development; Climatic changes; SCIENCE / Environmental Science; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography